COMPARISON OF ANTIMICROBIAL SENSITIVITY TO OLDER AND NEWER QUINOLONES VERSUS PIPERACILLIN-TAZOBACTAM, CEFEPIME AND MEROPENEM IN FEBRILE PATIENTS WITH CANCER IN TWO REFERRAL PEDIATRIC CENTERS IN TEHRAN, IRAN - Ali Nateghian; Joan Robinson; P. Vosough; M. Navidinia; M. Malekanl; A. Mehrvar; B. Sobuti; Pooria Bahadoran; Z. Gholinejad (Mediterranean Journal of Hematology and Infectious Diseases)
Infection in pediatric cancer patients has become a concerning problem due to increasing antimicrobial resistance. The goal of this study was to determine the antimicrobial resistance patterns of blood isolates from pediatric oncology patients in Iran to determine if quinolones are appropriate for empiric therapy.